Perancangan User Experience Aplikasi Cuti Online Telkom Indonesia Menggunakan Pendekatan Human-Centered Design (HCD) - Rida Nafianti; Herman Tolle; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Telkom Indonesia is a company that utilizes technology to manage leave. But on the implementation, there are still several obstacles to that leave management. One of them is when the employee wants to apply for leave but the head is not in place, leave approval cannot be given. Another obstacle is the process of leave submission cannot be monitored. Therefore, the redesign process is needed for desktop and mobile-based applications so the leave management process can be easier. The redesign process must be considered user experience therefore the application can long-lasting to be used by the user. This redesign process is used the Human-Centered Design (HCD) approach. HCD involves a human, perspective, in this case the users and stakeholders, in the whole process of developing solutions, which consist of several phases. The phase of specifying the context of use and the user requirements is carried out by interviewing Telkom Indonesia stakeholders and also observing pre-existing applications. From this process, the information obtained is there will be three users in the application, that is employee, admin, and approver, which each of them has different characteristics and tasks. The produced design solution phase is generated wireframe, screenflow, and high-fidelity prototype which is the final result of the application interface display later. The phase of evaluating the design carried out using the heuristic evaluation method by three evaluators. Total of nineteen problems found in the design solutions. From all the problems, there are five problems that are priorities for improvement. However, improvements were also made to other problems so as to leave as many as zero problems.